Effect of Pozzolanic Additives on the Strength Development of High Performance Concrete. (2017) - Dembovska, Laura; Bajare, Diana; Pundiene, Ina; Vitola, Laura
Abstract: The aim of this research is to estimate the effect of pozzolanic substitutes on the temperature generated by the hydration and on the final strength of concrete. Differential thermal analyses (DTA) were conducted. Ternary cementitious systems with different ratios of Portland cement, silica fume and calcined illite clay were investigated. The results showed that the rates of pozzolanic reaction and portlandite consumption in the silica fume-blended cement pastes are higher than in the illite clay-blended cement pastes.